DEVELOPMENT AND USABILITY EVALUATION OF A WEB-BASED SALES AND INVENTORY MANAGEMENT INFORMATION SYSTEM FOR MSMES USING RAPID APPLICATION DEVELOPMENT - Vina Ardelia Effendy; Shindy Arti; Nur Elah; Wiranti Kusuma Hapsari; Sarah Najla Hanifati (CV. Fahr Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) commonly face operational challenges in managing sales transactions and inventory records because of manual recording, non-integrated data, stock discrepancies, and delayed report preparation. This study aims to develop a web-based sales and inventory management information system for MSMEs using the Rapid Application Development (RAD) method and to evaluate its usability using the System Usability Scale (SUS). The RAD method was implemented through requirements planning, user design, rapid construction, and cutover stages, enabling iterative refinement based on user needs and feedback. The developed system includes dashboard monitoring, product management, customer and supplier management, sales and purchase transactions, automatic stock updates, inventory monitoring, low-stock detection, report generation, and user access management. System functionality was evaluated using black-box testing involving 20 test scenarios. The results showed that all tested functions were valid, resulting in a functional validity score of 100%. Usability evaluation was conducted using SUS with 15 respondents. The average SUS score was 85.33, indicating that the system was acceptable and had good usability. These findings show that the developed system can support MSMEs in improving transaction recording, inventory accuracy, stock monitoring, and report preparation. Therefore, integrating RAD-based development and SUS-based evaluation can produce a functional and usable information system for MSME sales and inventory management.